THE EFFECT OF PEER TUTOR METHOD ON READING ABILITY OF STUDENTS IN CLASS V SD INPRES NIPA-NIPA MAKASSAR CITY. - Irwanto Tandi; Munirah Munirah; Syafruddin Syafruddin (Universitas Tadulako, 2020)
he problem in this study is the low learning outcomes, especially in reading comprehension skills seen from the number of students who have not yet completed, so that the learning outcomes of VA class students 31.81% or about 7 students achieve mastery learning grades then class VB 40% or about 8 students achieve mastery learning values based on the KKM that has been determined is 67. The purpose of this study was to determine the effect of peer tutoring methods on the reading comprehension ability of grade V students of SD Inpres Nipa-Nipa Makassar. This type of research is experimental research. The technique of collecting data is done by using a test technique. Data collection tool in the form of multiple choice questions that have previously been tested which are analyzed with validity and reliability. Data analysis techniques in the form of quantitative. The results showed that the average value of the control class posttest was 70.67 while the average value of the experimental class was 76.55. Based on the results of the calculation of the hypothesis test shows the value of sig (2-tailed) 0.003, (0.003 <0.05) so that H0 is rejected. From these calculations it can be obtained that the peer tutoring learning model can affect student learning outcomes by 3% while the remaining 97% is influenced by variables or other factors not examined by researchers.Keywords: Peer Tutor Reading Comprehension Method.